1998
DOI: 10.1144/gsl.qjeg.1998.031.p4.08.
|View full text |Cite
|
Sign up to set email alerts
|

Experimental production of weathering nanomorphologies on carbonate stone

Abstract: Nanomorphological features ( c . > 1 mm) produced by weathering processes can be observed with SEM and allied techniques. An experimental study using acidic water sprayed onto marble and calcite substrates reveals that weathering nanomorphologies can be produced and classified, and their occurrence quantified. Comparison with field samples shows that the experimentally produced nanomorphologies are smaller than, but morphologically similar to, naturally occurring features. Further ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 6 publications
0
26
0
Order By: Relevance
“…Further investigation of individual factors controlling rock breakdown by salt attack has recently been suggested to be imperative (Rodriguez-Navarro and Doehne, 1998): the environmental conditions under which crystallization takes place, the characteristics of porous stones, the crystallization characteristics and growth patterns of salts, and the distribution of salts within porous stones, a function of solution flow and evaporation. Weathering research seems set to continue to be increasingly reductionist in the sense of integrating process at more detailed scales, particularly making use of microscope technology to examine process at micro-, or nano-, scales (Viles and Moses, 1998) and most recently, spectroscope technology (Edwards et al, 2002;Friolo et al, 2003).…”
Section: Reductionism and Weathering Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigation of individual factors controlling rock breakdown by salt attack has recently been suggested to be imperative (Rodriguez-Navarro and Doehne, 1998): the environmental conditions under which crystallization takes place, the characteristics of porous stones, the crystallization characteristics and growth patterns of salts, and the distribution of salts within porous stones, a function of solution flow and evaporation. Weathering research seems set to continue to be increasingly reductionist in the sense of integrating process at more detailed scales, particularly making use of microscope technology to examine process at micro-, or nano-, scales (Viles and Moses, 1998) and most recently, spectroscope technology (Edwards et al, 2002;Friolo et al, 2003).…”
Section: Reductionism and Weathering Studiesmentioning
confidence: 99%
“…5 illustrates the range of spatial scales across which regular pits may be observed on sandstone surfaces; arguably, a hierarchy of forms exists. Viles and Moses (1998) suggested that in the case of limestone dissolution microscale features may be diagnostic of specific processes and thus be used to predict the development of larger features. Links between micro-and mesoscale features on sandstone are tenuous, due largely to the polygenetic origin of most larger features; the assumption that microscale features remain constant is perhaps unfounded.…”
Section: Scale Issuesmentioning
confidence: 99%
“…A weathering system may exhibit wild spatial variability at a local (outcrop) scale, but on a broad scale resolves into a landscape dominated by climatic or structural controls. Conversely, the operation of weathering processes on individual grains and minerals, at nano-scales (Viles and Moses, 1998), is amenable to explanation by process mechanics, and does not display the pseudo-random spatial variation often seen on an outcrop.…”
Section: Weathering and Instabilitymentioning
confidence: 99%
“…For this purpose, SEM images of the surfaces of the rock slabs before and after the experiment were taken to examine the dissolution tracks formed during the acid attack. Typical dissolution morphologies in carbonate rocks under acid attack are etching, V-in-V etching, grain boundary widening, new precipitates, and etch pits [11]. The shape and deep of the marks is related to the strength of the acid attack.…”
Section: Dissolution Experimentsmentioning
confidence: 99%